Teachers’ perspective of the role of biological evolution in Biology teaching - Pedro Leonardo Guarilha Colli; Vinícius Colussi Bastos; Mariana Aparecida Bologna Soares de Andrade (Amazônia, 2022)
This study aimed to analyze the conceptions of Biology teachers regarding Biological Evolution and its teaching. This objective was traced considering that recent studies indicate that Biology is taught in a fragmented and memorized way. Several authors argue that Biological Evolution is the only element capable of integrating and giving meaning to Biological Sciences. However, studies indicate that many teachers need help understanding the idea and working with Evolution to unify biological knowledge. To understand the views of teachers regarding Biological Evolution and its teaching in Basic Education, this article adopted a qualitative perspective of analysis of an open questionnaire answered by 11 teachers working in different school contexts. The results and the interpretations produced corroborate other studies regarding the teachers' lack of understanding of the idea of Biological Evolution as the integrating axis of Biology and suggest that even those who understand do not put this perspective into practice. In addition, it was possible to perceive that many teachers have a distorted view of how they approach the topic, which may prevent them from adequately reflecting on the issue